AbsoluteNuts / Muhammad Haziq Auj Mohamad Izan - Mohamad Izan, Muhammad Haziq Auj (2021)
AbsoluteNuts is the name of the brand of our store. We are selling flavored assorted peanuts. The objective of this business is to provide consumer with a healthier snack choice by selling cheap, healthy, delicious and on the go snacks which can be consumed at any time. Our business began on Facebook on the 25th May 2021. We began by introducing just one assorted peanut flavor and adding two more flavor as our business goes on. Our breakthrough in the food and beverages market shows good feedback which signifies the successfulness of food and beverages products in the market. Since our commencement, AbsoluteNuts had received positive feedbacks and increasing in sales. This numbers are expecting to grow by the end of the year due to the increasing market reach that our product had achieve. As a result, it will give us increasing revenue and profits by the end of the year. As till this day, our assorted peanuts are still being shipped throughout the country as more people are consuming healthy snacks as their option for a better health.